Novel Insights Into the Effects of Interleukin 6 Antagonism in Non–ST‐Segment–Elevation Myocardial Infarction Employing the SOMAscan Proteomics Platform. Issue 12 (16th June 2020) - George, Marc J.; Kleveland, Ola; Garcia‐Hernandez, Jorge; Palmen, Jutta; Lovering, Ruth; Wiseth, Rune; Aukrust, Pål; Engmann, Jorgen; Damås, Jan Kristian; Hingorani, Aroon D.; Gullestad, Lars; Casas, Juan P.; et al.
Abstract : Background: Interleukin 6 concentration is associated with myocardial injury, heart failure, and mortality after myocardial infarction. In the Norwegian tocilizumab non–ST‐segment–elevation myocardial infarction trial, the first randomized trial of interleukin 6 blockade in myocardial infarction, concentration of both C‐reactive protein and troponin T were reduced in the active treatment arm. In this follow‐up study, an aptamer‐based proteomic approach was employed to discover additional plasma proteins modulated by tocilizumab treatment to gain novel insights into the effects of this therapeutic approach. Methods and Results: Plasma from percutaneous coronary intervention–treated patients, 24 in the active intervention and 24 in the placebo‐control arm, drawn 48 hours postrandomization were randomly selected for analysis with the SOMAscan assay. Employing slow off‐rate aptamers, the relative abundance of 1074 circulating proteins was measured. Proteins identified as being significantly different between groups were subsequently measured by enzyme immunoassay in the whole trial cohort (117 patients) at all time points (days 1–3 [7 time points] and 3 and 6 months). Five proteins identified by the SOMAscan assay, and subsequently confirmed by enzyme immunoassay, were significantly altered by tocilizumab administration. The acute‐phase proteins lipopolysaccharide‐binding protein, hepcidin, and insulin‐like growth factor‐binding protein 4 were all reduced during the hospitalization phase, as was the monocyte chemoattractant C‐C motif chemokine ligand 23. Proteinase 3, released primarily from neutrophils, was significantly elevated. Conclusions: Employing the SOMAscan aptamer‐based proteomics platform, 5 proteins were newly identified that are modulated by interleukin 6 antagonism and may mediate the therapeutic effects of tocilizumab in non–ST‐segment–elevation myocardial infarction.